Summer Freezing Resistance: A Critical Filter for Plant Community Assemblies in Mediterranean High Mountains - Pescador, David S.; Sierra-Almeida, Ángela; Torres, Pablo J.; Escudero, Adrián (Frontiers in Plant Science, 2016)
Assessing freezing community response and whether freezing resistance is related to other functional traits is essential for understanding alpine community assemblages, particularly in Mediterranean environments where plants are exposed to freezing temperatures and summer droughts. Thus, we characterized the leaf freezing resistance of 42 plant species in 38 plots at Sierra de Guadarrama (Spain) by measuring their ice nucleation temperature, freezing point (FP), and low-temperature damage (LT50), as well as determining their freezing resistance mechanisms (i.e., tolerance or avoidance). The community response to freezing was estimated for each plot as community weighted means (CWMs) and functional diversity, and we assessed their relative importance with altitude. We established the relationships between freezing resistance, growth forms, and four key plant functional traits (i.e., plant height, specific leaf area, leaf dry matter content, and seed mass). There was a wide range of freezing resistance responses and more than in other alpine habitats. At the community level, the CWMs of FP and LT50 responded negatively to altitude, whereas the functional diversity of both traits increased with altitude. The proportion of freezing-tolerant species also increased with altitude. The ranges of FP and LT50 varied among growth forms, and only the leaf dry matter content correlated negatively with freezing-resistance traits. Summer freezing events represent important abiotic filters for assemblies of Mediterranean high mountain communities, as suggested by the CWMs. However, a concomitant summer drought constraint may also explain the high freezing resistance of species that thrive in these areas and the lower functional diversity of freezing resistance traits at lower altitudes. Leaves with high dry matter contents may maintain turgor at lower water potential and enhance drought tolerance in parallel to freezing resistance. This adaptation to drought seems to be a general prerequisite for plants found in xeric mountains.